Student mobility in Ireland and Northern Ireland - Emer Smyth; Merike Darmody (The Economic and Social Research Institute (ESRI), 2023)
There has been an increasing focus in policy development internationally and in Ireland on the globalisation of higher education and student mobility. Consequently, a growing body of international research has focussed on the drivers of, and barriers to, studying abroad. Previous studies on this topic have highlighted a number of macro-, meso-, and micro-level factors that shape students' experiences. However, there has been relatively little systematic research on the institutional factors which potentially influence student mobility between Ireland, Northern Ireland and Britain. This study focuses on mobility for a whole undergraduate course (rather than mobility for an academic year or semester). It draws on administrative data, Central Applications Office (CAO) microdata, interviews with key stakeholders and a consultation event with stakeholders to address the following research questions: What is the level of student mobility between Ireland and Northern Ireland (and between NI and the other countries of the UK)? How has this changed over time, in particular during the pandemic? What factors are associated with student mobility? To what extent is there potential to increase student mobility across the island? And is this seen as a desirable objective by stakeholders?
Keywords: 330; Studierende; Mobilität; Studium; Irland; Nordirland; Großbritannien